PENDIDIKAN AGAMA, TANTANGAN TEKNOLOGI KOMUNIKASI, DAN TERORISME : INTRODUCTION - Syamsuri, Syamsuri (Universitas Nahdlatul Ulama Surakarta, 2024)
The aim of this research is to explain the importance of religious education to anticipate the challenges of communication technology and the dangers of terrorism through information on social media for teachers, students and the community. The method used is online research methods (ORM) and social network analysis (social media). The conclusion and implication is that information technology cannot be prevented and its benefits are in the midst of the needs of teachers, students and society, because the time has come. Religious education is very important to give to students from an early age, but it must be monitored so that they don't choose the wrong teacher or choose the wrong preaching link. This also results in people being out of control in receiving knowledge of the Islamic religion from certain scholars without learning directly from other scholars who are based on the Prophet Muhammad SAW, thus triggering friction between lack of brotherhood in society due to differences in khilafiyah. In the 21st century, religious education can easily be seen in the development of information technology which is experiencing very rapid progress in various corners of the world in general, especially in Indonesia. This also includes Islamic boarding school education which has become a popular educational institution in Indonesia since the beginning of the arrival of Islam in Indonesia in the 17th century. This has implications for teachers, students and society in understanding Islam.